Effect of adding germination wheat in diet Broiler and substituted for the yellow corn - Sabry, Suzan Waheed; AL-Fadhli, Murad Kadhim; Razooqi, Raad Hatem (Journal of agricultural, environmental and veterinary sciences, 2020)
This experiment was conducted to investigate the effect of germination on the chemical composition of wheat seeds and their inclusion in the diet on the productive characteristics of the broiler. germinate of wheat seeds was done at 25 c, for 72 hours and dried at 55-60 c.the germinated and none- germinated seeds were evaluated for chemical composition. For examining the effect germinated wheat on productive traits of broiler, we used 150 one day old chicks (Ross 308) were randomly divided to 5 treatments each with 3 replicates (10 chicks/ replicate). the experimental treatments were as follow (T1) corn 60% of the diet (control), (T2) corn 30%+ wheat 30% of the diet, (T3) corn 30%+ germinated wheat 30% of the diet, (T4) wheat 60% of the diet and (T5) germinated wheat 60% of the diet. the experiment lasted 42 days from 31/ 3/ 2019 to 5/ 5/ 2019. the results regarding chemical analysis showed there were significant (p< 0.05) increase in crud protein and carbohydrates, while the lipids and fibers were significantly lower(P<0.05) in germinated wheat compared with non-germinated wheat. on the other hand, the results indicated the use 30% corn+30% germinated wheat(T3) in the diet improved live body weight, weight gain and feed conversion ratio followed by the T5 (60% germinated wheat) which also achieved the best results especially in accumulate feed intake and feed conversion ratio. According to the results of this experiment, it can be concluded that germination improved the nutritive value of wheat and can be used as partially or entirely substituted for the yellow corn in broiler die.